Legislative and Judicial Response to Child Sexual Abuse (International Journal of Innovative Research in Engineering & Management, 2021)
Citizens of tomorrow are today's children. They are the  country's future. Child abuse is a terrible problem in India since  it is a rising and recurring problem; too many youngsters die or  get mistreated later in life. Abuse happens when someone  mistreats or exploits another person, with no regard for their  integrity or inherent value as persons, and in a way that  jeopardizes their well-being. Kid abuse is defined as an adult  inflicting significant physical or mental harm on a child.  Physical, sexual, neglect, and abandonment are all examples of  child abuse, as are emotional and psychic abuse. Youngster  abuse may be a lifelong problem and burden for the victimized  child. Pregnancy, or a new experience with sexual assault,  might reopen the survivor's traumas. The arousal of early  abuse-related trauma can also be triggered by approaching or  having attained middle age. As the survivor faces the  challenges of adulthood, the childhood legacy becomes  increasingly onerous. A shift in the balance of a close  connection is frequently the catalyst. The facade can no longer  withstand the pressure, and the underlying disintegration  emerges. When and if a breakdown happens, it might present  with symptoms that are similar to those of almost any mental  condition. Survivors are afraid of becoming mad or having to  die.
Keywords: Abuse; Child; Judicial; Legislative Sexual; Sexual Abuse